(3GdQjGV GdRGgQI aj TQM GdJPcQI GdaGNQIs - (3fLe GdOjf jhSa Hf CMeO Hf eMeO Hf YKeGfs ((3eMeO Hf bGSe Hf CMeO Hf bGSe s)
(3ChdgG (B:s
(3GdMeO ddg efTF GdfahS haGWQgG hHYO , adeG JcQQ WdH Gdabjg GdeYXe hGdMHQ GdWGgQ GdecQe CMeO Hf UGdM efUhQ CcQeg Gddg HGdZaQGf s
(3BNQgG (B:s
(3ajchf eG ai GdJPcQI ceG ai GdEaGOI , aGdMeO ddg Ydi cd MGd ef GdCbhGd s
(3GdfSNI HgG MhGTs
(3HMhGTjgG JYdjbGJs
(3cJHJ HQSe EHQGgje Hf CMeO Hf bGSe s
(3hcJHJ HYV GdYfGhjjf HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3abg GdePGgH GdCNQis